Clustering of Districts Based on Infrastructure Indicators Using K-Means And Average Linkage Methods - Eliza Agustia, Dewi; Fadhly, Noer; Zukhrina Oktaviani, Cut (Publisher Cv. Inara, 2025)
Aceh Jaya is one of the districts in Aceh Province that has great potential in various sectors, such as agriculture, plantations, and tourism. In the Aceh Jaya District Development Plan (RPK) Book 2023-2026, it is stated that the unequal distribution of infrastructure development in Aceh Jaya District in 2023-2026 has resulted in low investment competitiveness and decreased economic performance. Because of these conditions, this study clusters regions in Aceh Jaya District based on infrastructure indicators so that groups of sub-districts are obtained based on the level of infrastructure development. The method used in this study is clustering analysis by comparing it with two clustering methods, namely K-means and average linkage, which are validated based on the silhouette coefficient value to see which cluster is the best. The results obtained are the Kaiser-Mayer-Olkin (KMO) value of 0.611, which indicates that the sample is representative of a total of eight variables; for the zscore value, there is no outlier data, which means that the data of the eight infrastructure variables can be used entirely. Meanwhile, the clustering results using the K-Means method resulted in 3 clusters, and with the Average Lingkage method resulted in 2 clusters. This means that Aceh Jaya District can be clustered into 2 clusters, as seen from the silhouette coefficient value of 0.736. The conclusion that can be drawn from this research is that infrastructure development has not been evenly distributed in the 9 existing sub-districts, so that strategies and priorities are needed in infrastructure development in Aceh Jaya Regency.